Exploring the effects of import diversification on energy efficiency: Evidence from the OECD economies - Doğan, Buhari; Ferraz, Diogo [UNESP]; Gupta, Monika; Duc Huynh, Toan Luu; Shahzadi, Irum [UNESP] (Elsevier, 2022)
This study aims to unveil the heterogeneous impacts of import product diversification and institutional factors for achieving energy efficiency in Organization for Economic Co-operation and Development (OECD) countries. In doing so, the study employs robust econometric techniques such as Fully modified ordinary least squares (FMOLS) co-integration, pooled Ordinary Least Squares (OLS), Feasible Generalized Least Squares (FGLS), pool mean group regressions, fixed effects, and random effects for panel data from 1990 to 2015 for selected OECD countries. The detailed empirical outcomes suggest that import product diversification is conducive to reducing the energy and carbon intensity (improvement in energy efficiency) in OECD countries. The empirical conclusions provide various guidelines to achieve cleaner and greener growth and align with various Sustainable Development Goals (SDG 7: Affordable and clean energy, SDG 9: Industry, innovation, and infrastructure, and SDG 13: Climate action) of OECD countries. The paper elaborates fruitful policy suggestions regarding the diversification of imports and energy use-carbon emission-nexus for the OECD member nations. Based on the findings, policymakers and environmental scientists should strengthen the trade-energy and import portfolio policies to attain energy efficiency.
Keywords: Carbon intensity; Energy efficiency; Energy intensity; Import product diversification; OECD countries